2022
DOI: 10.1371/journal.pone.0279241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of multidimensional child poverty in India during 2015–2021: A multilevel analysis

Abstract: Despite increasing research and programs to eradicate poverty, poverty still exists and is a far greater concern for children than adults, leading child poverty to become a political, economic, and social issue worldwide and in India. The current study aims to find variations in the prevalence of child poverty and associated factors in India during 2015–21. In the current study, we used two consecutive rounds of the National Family Health Survey (NFHS-4, 2015–16 & NFHS-5, 2019–21) to estimate child poverty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…For example, the terrain type, per capita cultivated land area, and labor force ratio were significant at the village level, while the per capita income, vegetation coverage, and terrain relief were significant at the county level [35]. The multilevel analysis of multidimensional child poverty in India showed that the age and sex of the child, age and years of schooling of the mother, children ever born, religion, caste, wealth quintile, and central, northeast, north and west regions are significantly associated with child poverty [36].…”
Section: The Scale Effects Of Regional Povertymentioning
confidence: 94%
“…For example, the terrain type, per capita cultivated land area, and labor force ratio were significant at the village level, while the per capita income, vegetation coverage, and terrain relief were significant at the county level [35]. The multilevel analysis of multidimensional child poverty in India showed that the age and sex of the child, age and years of schooling of the mother, children ever born, religion, caste, wealth quintile, and central, northeast, north and west regions are significantly associated with child poverty [36].…”
Section: The Scale Effects Of Regional Povertymentioning
confidence: 94%